Exploring the similarity between Han's and non-Han's Yuan poetry: Resistance distance metrics over character co-occurrence networks. - Yang, Yi; Song, Yue (Digital Scholarship in the Humanities, 2022)
The Yuan dynasty is the first non-Han unified dynasty in ancient China. It is subtle to tell the similarities and differences between the classic Chinese poems in the Yuan dynasty written by the writers of Han nationality and non-Han minority nationalities. By graph theory and statistics, this article establishes a novel method for quantifying the similarity between the Han's and non-Han's Yuan poetry. First, we formulate the character co-occurrence networks (CCONs) of the Han's and non-Han's Yuan poem databases collected from 'Database of Ancient Chinese Classics'. The resistance distance, a graph theory concept, is introduced to describe the lexical relation between a pair of characters in the CCONs. Then, we propose the similarity index as the coefficient of variation for the ratios of resistance distances in the CCONs of Han's and non-Han's poem databases, which measures the consistency between the usages of characters in the Han's and non-Han's poems. The calculation results indicate that the Han's and non-Han's poems share a high percentage of common high-frequency characters and there do not exist significantly different lexical features in terms of the usage of these high-frequency characters. The obtained results offer new insights into the quantitative features of this long-debated issue.